ANOMALI PEMBELAJARAN BERDIFERENSIASI SEBAGAI TANTANGAN IMPLEMENTASI KURIKULUM MERDEKA DI SEKOLAH DASAR - Rahayu, Ade (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Differentiated learning (DL) is considered a strategic solution to address student diversity in learning readiness, interests, and learning profiles in elementary schools (SD). However, there are still some problems in implementing it, mainly because teachers believe that PB means creating completely different lesson plans for each student. Thus, this phenomenon creates a discrepancy between theory and practice. In this case, the inclusive approach actually adds to the teacher's burden rather than improving the learning process. The Merdeka Curriculum, which requires a customized approach, makes this issue even more important. The purpose of this study is to identify and analyze inconsistencies in the implementation of PB in elementary schools, particularly regarding the differences between the ideal concept and the reality on the ground. The research also attempts to identify the main barriers stemming from perceptions and support structures. The research employed the Systematic Literature Review (SLR) method, which involved bibliometric and thematic analysis of twenty scientific articles obtained from the Sinta database (2020–2025). After data was collected thru a systematic search using relevant keywords, a thorough analysis was conducted to identify key themes, supporting elements, and constraints. The results show that the main problem is not a lack of conceptual understanding, but how teachers perceive the complexity of PB, which leads to resistance. This condition is made worse by structural issues such as time constraints and administrative responsibilities. PB increases motivation and learning outcomes, but its implementation is often ineffective. This study provides novelty by identifying PB anomalies as a